The Relevance of Modern Management in Sharia Economics: A Value and Professionalism Approach - Khairan; Nurfitriani, Ika (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Purpose/Objectives – The objectives of this article are to analyze the relevance of modern management principles from a Sharia economics perspective, identify similarities and possible differences between the orientation of efficiency in modern management and Islamic values, and formulate a conceptual framework that combines modern management, Islamic values, and professionalism in a complementary model. Method – This study employs a qualitative research approach, utilizing a library-based research method, with data sources comprising modern management literature, Islamic economics, scientific journal articles, and normative Islamic sources. Data analysis was conducted descriptively, analytically, conceptually, and comparatively to identify the compatibility between modern management principles and Islamic economic values. Findings – The study's results indicate that modern management principles align closely with Sharia values, including tauhid, amanah, justice, ihsan, and maslahah, when applied within the framework of Islamic ethics. Professionalism, which encompasses itqan, competence, amanah, and responsibility, serves as the integrative meeting point between modern management and Sharia economics. Limitations – The use of a qualitative approach, based on library research, which is conceptual and normative in nature, means that empirical field data do not support the study's results. This study did not directly observe the practice of modern management in specific Islamic economic institutions, so it was unable to describe the dynamics of implementation, operational challenges, and variations in institutional contexts in a factual manner. In addition, the data sources used were limited to literature, scientific journals, and normative Islamic sources, which could potentially lead to limitations in perspective due to differences in conceptual interpretation among authors. Originality/Value – This article emphasizes that modern management is not a concept that conflicts with Islamic economics, but rather a strategic instrument for realizing professional, ethical, and welfare-oriented management of Islamic economic institutions.